Investigating the Banking Sector Development Transmission Mechanism of Financial Development to Growth: Evidence from Sub-Saharan Africa (SSA) - Tochukwu Timothy Okoli; Ajibola Rhoda Oluwafisayomi (Journal of Economics and Behavioral Studies, 2019)
The search for financial development’s transmission channel to growth has always been updated in the literature. While there has not been a consensus on this matter, empirical findings on finance-growth nexus have been ambiguous. Relying on this, we investigate its bank development transmission channel to growth in a panel of twenty-eight Sub-Saharan Africa (SSA) countries from 2000-2016. Having adopted the augmented Solow (1956) and Mankiw et al. (1992) growth model, the fixed effect and dynamic system GMM estimation techniques reveals a negative non-significant and positive significant direct impact of finance on growth in the static and dynamic models respectively, thereby suggesting institutional (dynamic) factors that can spur finance. Secondly, the non-linear effects of bank development had a direct positive significant impact on growth and its marginal-effects before and after the financial crisis of 2007/08 were relatively stable. This implies that banks in SSA were relatively stable in financial intermediation; therefore SSA countries need to reinforce and improve its banking policy through FinTechs adoption. Finally, the interaction between bank development and financial development significantly increase steady-state growth. This implies that SSA economies can promote steady-state growth from financial development only when a threshold of bank development is reached.